2013
DOI: 10.1242/jcs.127829
|View full text |Cite
|
Sign up to set email alerts
|

Cullin5 destabilizes Cas to inhibit Src-dependent cell transformation

Abstract: Phosphorylation-dependent protein ubiquitylation and degradation provides an irreversible mechanism to terminate protein kinase signaling. Here, we report that mammary epithelial cells require cullin-5-RING-E3-ubiquitin-ligase complexes (Cul5-CRLs) to prevent transformation by a Src-Cas signaling pathway. Removal of Cul5 stimulates growth-factor-independent growth and migration, membrane dynamics and colony dysmorphogenesis, which are all dependent on the endogenous tyrosine kinase Src. Src is activated in Cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(67 citation statements)
references
References 55 publications
1
66
0
Order By: Relevance
“…We previously reported that Cul5 inhibits the epidermal growth factor (EGF)-independent migration of MCF10A epithelial cells (Teckchandani et al, 2014). Cul5-depleted cells migrate considerably faster than control cells and have an exaggerated leading lamellipodium bearing tiny FAs, few stress fibers and dynamic membrane ruffles.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that Cul5 inhibits the epidermal growth factor (EGF)-independent migration of MCF10A epithelial cells (Teckchandani et al, 2014). Cul5-depleted cells migrate considerably faster than control cells and have an exaggerated leading lamellipodium bearing tiny FAs, few stress fibers and dynamic membrane ruffles.…”
Section: Resultsmentioning
confidence: 99%
“…The full picture is more complicated, however. Combined knockdown of several SOCS proteins is required to stimulate cell migration to the same extent as Cul5 (130). SOCS7 knockdown stimulates migration of some cancer cell lines (134).…”
Section: Cell Regulation By Crl5: Studies With Cul5 and Rbx2mentioning
confidence: 99%
“…Along these lines, the removal of Cul5 and/or Rbx2 from fibroblasts, epithelial cells, and developing brain increases the level of active but not inactive Src and Fyn proteins but not mRNA (128,(130)(131)(132)(133). This suggests that CRL5 complexes regulate Src/Fyn stability, but changes in half-life have not been reported.…”
Section: Cell Regulation By Crl5: Studies With Cul5 and Rbx2mentioning
confidence: 99%
See 1 more Smart Citation
“…[31] Moreover, silencing CUL5 reduces cellular sensitivity, and endogenous CUL5 suppresses epithelial cell transformation by several pathways, including inhibition of Src-Cas-induced ruffling through SOCS6. [32,33] In the cellular component, the genes in module 3 are principally localized in the nucleus, signalosome, protein complex, and macromalecular complex. The genes in module 71, which are principally detected in the mitochondrial inner membrane presequence translocase complex, participate in protein localization in the mitochondrion and protein targeting to the mitochondrion.…”
Section: Function Enrichment Of Differentially Expressed Modulesmentioning
confidence: 99%